INCREASING CUSTOMER LOYALTY THROUGH SERVICE QUALITY AND CUSTOMER SATISFACTION IN THE DIGITAL ERA - Adi Sofyana Latif; Teguh Setiawan Wibowo; Tanti Widia Nurdiani; Erina Alimin; Yayat Suharyat (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research is motivated by the importance of consumer loyalty for companies. This study aims to determine and analyze the effect of service quality and customer satisfaction on customer loyalty in the Digital Era. The research method used in this research is descriptive method with a quantitative approach. The sample in this study were 100 consumers using a random sampling technique. Collecting data using questionnaires distributed to consumers. The instruments used have been tested for validity and reliability. The collected data were analyzed using the classical assumption test and multiple linear regression using excel and SPSS. The results of this study indicate that 1) Service quality has a positive and significant effect on consumer loyalty in the digital era, 2) Customer satisfaction has a positive and significant effect on customer loyalty in the digital era, and 3) Service quality and customer satisfaction have a positive and significant effect on customer loyalty in the digital Era. The findings of this study indicate that if companies want to increase consumer loyalty, companies must also improve service quality and customer satisfaction in the digital era.